Evaluation system of tourism endowment destination based on tourism endowment index - Pang, Xiaoxiao; Ramachandran, Sridar; Siow, May Ling; Subramaniam, Thanam (Human Resource Management Academic Research Society, 2023)
The destination is the foundation for tourism endowment activities; however, the majority of relevant studies focus on how to develop and build tourism endowment destinations, with little attention paid to site selection, particularly the construction of a scientific evaluation system for tourism endowment destinations. A relatively scientific evaluation system will aid in guiding tourism endowment's work, contribute to the region's tourism endowment industry's development, and improve the quality of life for urban residents and tourists. Taking China as an example, this paper compiles previous research on livable, endowment, remote endowment, and pension tourism, and uses Delphi and Logarithmic Fuzzy Priority Programming- Fuzzy Analytic Hierarchy Process (LFPP-FAHP) to develop an evaluation index system for tourism endowment destinations using the tourism endowment index (TEI). This index system consists of three criterion layers, ten field layers, and 35 index layer indexes for endowment living environment, ecological environment, and tourism environment, and these indexes have been modified using the Delphi method to be beneficial for the construction and research of tourism endowment index, industry, and destination.